Ability to Construct Geogebra-Assisted Proofs in View of Gender Differences - Mone, Ferdinandus; Simarmata, Justin Eduardo; Nahak, Selestina (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2025)
The ability of Mathematics Education students at Unimor to prove mathematical statements is relatively low. The ability to construct proofs in learning the concept of function limits is very important for advanced calculus material. The purpose of this study is to analyze the ability of male and female students in constructing proofs after being taught using GeoGebra as a learning medium. The research findings show that female students have superior proof construction abilities compared to male students. Female students excel in organizing facts, manipulating facts, and sequencing proof steps.